2023
DOI: 10.1371/journal.pntd.0011020
|View full text |Cite
|
Sign up to set email alerts
|

Individual variation in Plasmodium vivax malaria risk: Are repeatedly infected people just unlucky?

Abstract: Extensive research has examined why some people have frequent Plasmodium falciparum malaria episodes in sub-Saharan Africa while others remain free of disease most of the time. In contrast, malaria risk heterogeneity remains little studied in regions where P. vivax is the dominant species. Are repeatedly infected people in vivax malaria settings such as the Amazon just unlucky? Here, we briefly review evidence that human genetic polymorphism and acquired immunity after repeated exposure to parasites can modula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 81 publications
1
3
0
Order By: Relevance
“…The distribution of malaria types, specifically P. falciparum and P. vivax infections, was similar between patients with and without G6PD deficiency. Although no statistically significant differences were observed, the higher proportion of P. vivax infections among G6PD-deficient patients is consistent with previous studies (14,21,22) that have reported an association between G6PD deficiency and increased susceptibility to P. vivax malaria. Among the hematological parameters analyzed, the study found a noteworthy difference in the mean monocyte count between patients with G6PD deficiency and those without G6PD deficiency.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The distribution of malaria types, specifically P. falciparum and P. vivax infections, was similar between patients with and without G6PD deficiency. Although no statistically significant differences were observed, the higher proportion of P. vivax infections among G6PD-deficient patients is consistent with previous studies (14,21,22) that have reported an association between G6PD deficiency and increased susceptibility to P. vivax malaria. Among the hematological parameters analyzed, the study found a noteworthy difference in the mean monocyte count between patients with G6PD deficiency and those without G6PD deficiency.…”
Section: Discussionsupporting
confidence: 91%
“…Understanding the hematological markers of G6PD deficiency in individuals infected with malaria is crucial for effective diagnosis, management, and prevention of associated complications. Malaria, a parasitic infection transmitted through the bite of infected mosquitoes, poses a significant health burden in many parts of the world, particularly in regions where G6PD deficiency is prevalent (13,14). The interaction between G6PD deficiency and malaria infection is complex, as certain antimalarial medications, such as primaquine, can induce severe hemolysis in G6PD-deficient individuals (15).…”
Section: Introductionmentioning
confidence: 99%
“…While our results could be explained by a simultaneous outbreak of both Po species, the mosquito feeding assays depicted in Table 4 spanned two years of data collection. Rather, those exposed to one Po species may be more likely to also be exposed to the other Po species, with malaria exposure concentrated in a small proportion of the population who then serve as a reservoir [ 40 ]. The role of relapse, in which persons once exposed remain latently infected in the liver, could also contribute to unexpected high rates of co-infection.…”
Section: Discussionmentioning
confidence: 99%
“…species may be more likely to also be exposed to the other Po species, with malaria exposure concentrated in a small proportion of the population who then serve as a reservoir [40]. The role of relapse, in which persons once exposed remain latently infected in the liver, could also contribute to unexpected high rates of co-infection.…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%